1995
DOI: 10.1080/09540129550126803
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in HIV-related psychological distress in heterosexual couples

Abstract: In order to determine the effect of family support on the psychological well-being of heterosexual couples with at least one HIV-seropositive, family support data were obtained from couples, who were separately interviewed. Two hundred heterosexuals were interviewed (97 males, 103 females). 182 were partners in HIV serodiscordant couples (18 members were in 10 couples concordant for HIV-seropositivity). Overall, there were 76 HIV+ males and 30 HIV+ females. The Brief Symptom Inventory (BSI) was used to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 6 publications
(6 reference statements)
3
30
0
2
Order By: Relevance
“…In fact, in the present study, the affected mother/unaffected father pairs tended to have higher mean depression scores than affected father/unaffected mother pairs. Although experts disagree on the explanation [e.g., Gove, 1984;Verbrugge, 1985], women have been shown to experience greater levels of distress than men when facing stressors such as colon cancer [Cella et al, 1987;Baider et al, 1989;Northouse et al, 2000], HIV [Kennedy et al, 1995], and natural disaster [Steinglass and Gerrity, 1990]. One study found that women affected with colorectal cancer were more distressed than their husbands at the time of diagnosis and 60 days after surgery [Northouse et al, 2000].…”
Section: Discussionmentioning
confidence: 96%
“…In fact, in the present study, the affected mother/unaffected father pairs tended to have higher mean depression scores than affected father/unaffected mother pairs. Although experts disagree on the explanation [e.g., Gove, 1984;Verbrugge, 1985], women have been shown to experience greater levels of distress than men when facing stressors such as colon cancer [Cella et al, 1987;Baider et al, 1989;Northouse et al, 2000], HIV [Kennedy et al, 1995], and natural disaster [Steinglass and Gerrity, 1990]. One study found that women affected with colorectal cancer were more distressed than their husbands at the time of diagnosis and 60 days after surgery [Northouse et al, 2000].…”
Section: Discussionmentioning
confidence: 96%
“…Both HIV-positive men and women have been shown to have psychological distress associated with HIV infection [51,52], and most studies have shown evidence that women usually reported higher psychopathogical symptoms or psycholocical co-morbidity than men [53][54][55]. According to Vosvick and colleagues [5], across multiple samples of PLWHA, it is evident that men and women differ in symptoms, behaviors, and other conditions, which greatly influences well-being.…”
Section: Psychopathological Symptomsmentioning
confidence: 93%
“…In general these studies have found that women tend to experience high levels of psychological distress and that the levels they experience are probably, on average, as great or greater than those experienced by men. Relative to HIV-infected men, HIV-infected women have been shown to report scores indicative of significantly poorer adjustment on measures of mental health (Wachtel et al, 1992); psychological distress, including subscales of depression and anxiety (Kennedy, Skurnick, Foley, & Louria, 1995), depression (Linn, Poku, Cain, Holzapfel, & Crawford, 1995;Linn Anema, Hodess, Sharpe, & Cain, 1996;Cleary et al, 1993), and anger (Anderson, 1995).…”
Section: Introductionmentioning
confidence: 99%